Using concept maps to evaluate preservice biology teachers’ conceptualization of COVID-19 as a complex phenomenon - Bielik, Tom; Jagemann, Johannes; Krell, Moritz; Krüger, Dirk; Ben Zvi Assaraf, Orit (Frontiers in Education, 2023)
The Covid-19 pandemic showed the critical importance of supporting teachers’ and students’ systems thinking when making sense of complex phenomena. This study sets to explore preservice biology teachers’ (PBTs, N=27) mental models of Covid-19 as complex phenomenon using concept maps. Structural and complexity attributes were identified in participants’ concept maps and tested the relationships between them, providing statistical analyses using exemplary concept maps. It was found that most concept maps did not address the highly complex chain of events describing how the Covid-19 outbreak spread out, and only few maps demonstrated high level of cross-level reasoning. Additional interviews were conducted with three PBTs to support the analysis and interpretation. The results suggest that the appearance of many concepts in a map (structural attribute) does not necessarily indicate high level of complexity, but rather the amount of simple structural relationships (complexity attribute). On the other hand, the results indicate that higher structural sophistication (e.g., high number of connections and junctions) could be associated with the complexity level of the map. This study provides a practical method for evaluating the complexity level of PBTs’ systems thinking, suggests a possible link between structural and complexity attributes in their concept maps, and demonstrates the need to further support PBTs in developing their systems thinking skills in the context of complex biological phenomena.